growth, carcass production and meat quality of ongole grade cattle, simmental ongole crossbred cattle and brahman cross - Ngadiyono, Nono (2015)
The experiment was conducted to study the growth rate, carcass production and meat quality of Ongole grade (PO), Simmental Ongole crossbred (SimPO) and Brahman cross (BX) cattle grown in a feedlot system for 3 months. The study were used five head of PO, seven head of SimPO and six head of BX cattle with the respective initial body weight of 307.70+25.72 kg; 353.07+27.95 kg; and 357.00+52.24 kg. The age of cattle about 1.5-2.5 years. The cattle were fed with concentrates and elephant grass. At the end of the experiment all cattle were slaughtered. Meat samples used were Longissinus dorsi (LD) muscles. The variables observed were feed consumption, average daily gain (ADG), feed conversion ratio (FCR), carcass percentage, carcass components, meat physical quality and chemical composition. The obtained data were analyzed by using the analysis of variance of the completely random design and Duncan’s new multiple-range test. The results showed that there were significant differences (P < 0.05) on the growth variable of feed consumption, ADG and FCR. The feed consumption of BX cattle was higher than PO cattle, but was not significant differences between SimPO and BX, as well as between SimPO and PO cattle. ADG of BX cattle was higher than SimPO and PO cattle. FCR of PO cattle was higher than SimPO and BX cattle, but was not significantly different between SimPO and BX cattle. The percentage of carcass, meat, bone and meat-bone ratio were not significant differences between the cattle breeds. The physical quality of meat (water-holding capacity, cooking loss, tenderness) were significant differences (P < 0.05) between the breeds, but the pH did not differ significantly. The meat chemical composition (water, fat, ash content) were not significant differences, but the protein content was differ significantly (P < 0.05). It could be concluded that the growth of BX cattle were better than SimPO and PO, but SimPO was better than PO. The meat of PO and SimPO cattle were higher water-holding capacity than meat of BX cattle, but meat of BX cattle was more tender than meat of PO and SimPO cattle. Key Words: Growth, Carcass, Meat Quality, Ongole Grade Cattle, Simmental Ongole Crossbred Cattle and Brahman Cross.